Extraintestinal Pathogenic Escherichia coli: A Combination of Virulence with Antibiotic Resistance - Pitout, Johann (Frontiers in Microbiology, 2012)
Escherichia coli represents an incredible versatile and diverse enterobacterial species and can be subdivided into the following; i) intestinal non-pathogenic, commensal isolates. ii) intestinal pathogenic isolates and iii) extraintestinal pathogenic or ExPEC isolates. The presence to several putative virulence genes has been positively linked with the pathogenicity of ExPEC. E. coli remains one of the most frequent causes of nosocomial and community-acquired bacterial infections including urinary tract infections, enteric infections, and systemic infections in humans. ExPEC has emerged in 2000’s as an important player in the resistance to antibiotics including the cephalosporins and fluoroquinolones. Most importantly among ExPEC is the increasing recognition of isolates producing “newer -lactamases” that consists of plasmid-mediated AmpC β-lactamases (e.g. CMY), extended-spectrum -lactamases (e.g. CTX-M), and carbapenemases (e.g. NDM). This review will highlight aspects of virulence associated with ExPEC, provide a brief overview of plasmid-mediated resistance to β-lactams including the characteristics of the successful international sequence types such as ST38, ST131, ST405 and ST648 among ExPEC.